2010
DOI: 10.1007/s10198-010-0252-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of disease severity on EQ-5D and SF-6D utility discrepancies in chronic heart failure

Abstract: In subgroups of patients differing in CHF severity according to the DASI, mean EQ-5D and SF-6D indices differed significantly. Contrarily, in socio-demographic and clinical groups, these utility differences were not directly evident. According to the evidence, comparisons based on severity classification via a valid disease-specific external instrument may provide insight on instrument choice in cost-utility analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 47 publications
3
20
1
1
Order By: Relevance
“…As shown in Supplemental Content 4, http://links.lww.com/CCM/B175), the EQ-5D scores for frail survivors in our study were lower than those reported in the literature for several chronic diseases (35)(36)(37)(38). Similarly, the EQ-5D scores for frail survivors were also markedly lower when compared with scores reported by ICU survivors (10,30,39).…”
Section: Association Of Chronic Disease Critical Illness Syndromes contrasting
confidence: 82%
See 1 more Smart Citation
“…As shown in Supplemental Content 4, http://links.lww.com/CCM/B175), the EQ-5D scores for frail survivors in our study were lower than those reported in the literature for several chronic diseases (35)(36)(37)(38). Similarly, the EQ-5D scores for frail survivors were also markedly lower when compared with scores reported by ICU survivors (10,30,39).…”
Section: Association Of Chronic Disease Critical Illness Syndromes contrasting
confidence: 82%
“…Prehospital frailty (CFS > 4) was present in 33% (n = 138; 95% CI, [28][29][30][31][32][33][34][35][36][37][38]. Baseline characteristics stratified by frailty are shown in Table 1.…”
Section: Characteristics and Outcomes Of Frail Patientsmentioning
confidence: 99%
“…In 2011, Soler et al reported the first prospective study evaluating utility outcomes following ESS for patients with refractory CRS . Using the SF‐6D health‐state utility questionnaire, they demonstrated a baseline CRS utility value of 0.65 (95% confidence interval, 0.63‐0.66), which was lower than other chronic conditions such as congestive heart failure and chronic obstructive pulmonary disease . With a mean follow‐up of 1.5 years after ESS, the utility score increased by 0.087 (95% confidence interval, 0.06 −0.12) to provide a mean overall short‐term post‐ESS utility value of 0.74.…”
Section: Discussionmentioning
confidence: 99%
“…If the same association between SES and HRQL could also be found among patients with diabetes mellitus, for example, this would clearly indicate two potential problems: health inequalities would be underestimated if HRQL is not assessed, and policy recommendations based on HRQL analyses could be biased if the differences according to SES are not stressed. Although not primarily devoted to the investigation of SES, most of these studies include SES in the analysis of HRQL, looking at a specific group of patients such as patients with heart attack [34], myocardial infarction [35], type 2 diabetes [36], chronic low back pain [37], chronic obstructive pulmonary disease (COPD) [38], depression [39] or patients undergoing elective cardiac surgery [40] or percutaneous coronary intervention (PCI) [41]. Other studies are based on population surveys including different chronic diseases [33,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Some report that the positive association between SES and HRQL is significant either for men or for women or for specific indicators of SES [37]. Others show that this association is significant only for the EQ-5D-3 L time trade-off (TTO) valuation, but not for the EQ-5D-3 L Visual Analog Scale (VAS) [40]. Some indicate that this association is not statistically significant [39], and some do not even include a statistical test for this association [33,42].…”
Section: Introductionmentioning
confidence: 99%